Estudio para la construcción de una línea de subtransmisión de 69 kv “guanujo-simiatug”, perteneciente a la provincia Bolívar - Bonilla Segura, Viviana Elizabeth (2017)
The Public Company CNEL EP BOLIVAR, in order to increase demand for energy in the part of Guaranda in Simiatug due to the distance that is served as the current substation by the increase of customers in order to implement the efficient cooking plan, it has planned the construction of subtransmission line to 69 kV which will start from Guanujo substation and it will arrive to Simiatug substation located in Guaranda -Simiatug The line projected has a length of 28.68 km, it is formed by a simple circuit triphase, with Aluminum Conductor ACSR type, size 266.8 MCM, which they will be put through porcelain insulators to reticulated metal structures, according to show the drawing. The line is designed with supporting structures, in other words, it does not consider the installation of tensors at any stage. For protection against atmospheric discharges at the top of the metal towers it will be installed optic fiber cable type Optical Ground Wire (OPGW) of 24 fibers….